Front Cover Image. Issue 1 (27th January 2022) - Zhang, Xin; Zhang, Wenqing; Dai, Jianying; Sun, Mingzi; Zhao, Jun; Ji, Lifei; Chen, Lin; Zeng, Fanlong; Yang, Fengchun; Huang, Bolong; Dai, Liming
Abstract : Since most electrocatalysts for oxygen evolution reaction (OER), except for precious metal oxides RuO2 and IrO2, are unstable in harsh acidic solutions, it is highly desirable to develop high‐performance OER electrocatalysts for acidic media. Herein, authors (DOI: 10.1002/inf2.12273 )report a simple strategy to produce carboxyl‐enriched multiwalled carbon nanotubes that exhibit stable and high electrocatalytic activities for OER in acidic solutions. As far as we are aware, these results represent the best OER performance for metal‐free electrocatalysts, even comparable to those of RuO2 and IrO2. Abstract : Since most electrocatalysts for oxygen evolution reaction (OER), except for precious metal oxides RuO2 and IrO2, are unstable in harsh acidic solutions, it is highly desirable to develop high‐performance OER electrocatalysts for acidic media. Herein, authors (DOI: 10.1002/inf2.12273 )report a simple strategy to produce carboxyl‐enriched multiwalled carbon nanotubes that exhibit stable and high electrocatalytic activities for OER in acidic solutions. As far as we are aware, these results represent the best OER performance for metal‐free electrocatalysts, even comparable to those of RuO2 and IrO2.